Applications of Differential Inequalities Employing A New ConvolutedOperator Constructed by The Supertrigonometric Function - Abdulnaby, Zainab E.; Ibrahim, Rabha W. (Iraqi Journal of Science, 2024)
In order to examine various geometric features, we expanded the supertrigonometric function (STF) and superhyperbolic function (SHF) into the open unit disk. A convolution differential operator of the STF provides the formulas. The suggested operator works with both integral and double differential inequalities. As a result, we present a collection of findings that includes recent works. The idea ofsubordination and superordination serves as a guide for our method, and we then developed the primary conclusion as a double side’s theorem.